Differences in technical and tactical efficiency between winning and defeated water polo teams: A comparative analysis - Hraste, M.; Bulic, K. A.; Jelaska, I. (SportMont, 2023)
Notation analysis is basically the gathering and analyzing of information that has been gained from observing performance in a competitive situation. The aim of this paper was to determine and explain the results and differences in technical and tactical efficiency in men`s water polo between winning and defeated teams. The sample of the entities included 31 matches from the men`s tournament held at the Olympic Games in Tokyo 2021. The sample of variables covered 18 defense and attack parameters of efficiency. Using a t-test for independent samples led to a result that the winning and losing teams differed significantly in four variables. Significant differences of winning teams in the realization with an equal number of players was probably stemmed from having better skills in achieving optimal conditions in preparation and performance. The reasons for the superiority of the winning teams in the part of defensive actions can probably be found in better and more coordinated actions of all defensive players in exclusions, blocking the ball and goalkeeper shot saves. These findings encourage coaches to improve players` skills by providing optimal conditions for the part of the technical-tactical solutions in defense and attack.